2012
DOI: 10.1021/jp209476h
|View full text |Cite
|
Sign up to set email alerts
|

Perrhenate Complexation by Uranyl in Traditional Solvents and in Ionic Liquids: A Joint Molecular Dynamics/Spectroscopic Study

Abstract: The complexation of perrhenate (ReO(4)(-)) anions by the uranyl (UO(2)(2+)) cation has been investigated by joint molecular dynamics simulations and spectroscopic (UV-vis, TRLFS, and EXAFS) studies in aqueous solution, acetonitrile, and three ionic liquids (ILs), namely, [Bmi][Tf(2)N], [Me(3)BuN][Tf(2)N], and [Bu(3)MeN][Tf(2)N] that are based on the same Tf(2)N(-) anion (bis(trifluoromethylsulfonyl)imide) and either Bmi(+) (1-butyl,3-methylimidazolium), Me(3)BuN(+), or Bu(3)MeN(+) cations. They show that ReO(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 80 publications
4
22
0
Order By: Relevance
“…For other complexed anions, such as the ReO 4 − , Br − , Tf 2 N − , CF 3 SO 3 − , and ClO 4 − , their interactions with uranyl ions have also been studied extensively. Chaumont et al studied the interaction of ReO 4 − with uranyl ions in Tf 2 N − ‐based ionic liquids. The EXAFS results showed that centered uranium was surrounded by 5 equatorial oxygen atoms at average U‐O distances of 2.43 Å, which decreased slightly with the Re/U ratio up to 10.…”
Section: Determination Of Actinide Speciation By Xafsmentioning
confidence: 99%
“…For other complexed anions, such as the ReO 4 − , Br − , Tf 2 N − , CF 3 SO 3 − , and ClO 4 − , their interactions with uranyl ions have also been studied extensively. Chaumont et al studied the interaction of ReO 4 − with uranyl ions in Tf 2 N − ‐based ionic liquids. The EXAFS results showed that centered uranium was surrounded by 5 equatorial oxygen atoms at average U‐O distances of 2.43 Å, which decreased slightly with the Re/U ratio up to 10.…”
Section: Determination Of Actinide Speciation By Xafsmentioning
confidence: 99%
“…and [UO 2 (CH 3-CN) 5 ] 2? dications is also evaluated (Chaumont et al 2012;Kulyukhin and Kamenskaya 2010). As the quantitation by ESI-MS and MALDI-MS method is conceptually different, due to different, virtually continuous and pulsed ionization techniques, the sensitivity and reproducibility are discussed comprehensively.…”
Section: Mass Spectrometric Methods Developmentmentioning
confidence: 99%
“…The environmental speciation, thereby, has involved complex (bio)geochemical reactions in solution, sorption/desorption processes onto minerals, biological processes causing distribution of uranium various oxidation states and chemical compositions (Conradson et al 2004;Malliakas et al 2012;Lee et al 2009;Chaumont et al 2012;Park et al 1990;Van Horn and Huang 2006). In parallel, the minerals themselves near to geosphere, when they are exposed to the effect of aerobic atmospheric conditions are oxidized and/or decomposed yielding different oxidative products, thus causing different uptake behavior of heavy metals in the environment, particularly reflecting in mind uranium and other radionuclides (Scott et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations